STUDENTS’ ATTITUDE TOWARDS CORRECTIVE FEEDBACK IN EFL CLASSROOM - Retno Wiyati; Rosa Padzilah Nur (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2020)
This research is conducted to find out the teacher’s corrective feedback in an EFL classroom and to find out the students’ attitude after given corrective feedback. This research also tries to unfold the types of the teacher’s corrective feedback to correct the student’s erroneous or mistakes and what students’ attitude after given the correction. This research is conducted in one high school in Bandung. The research employed a descriptive qualitative study embracing the characteristics of a case study research design. In collecting the data, the researcher conducted classroom observation and interview. The observation sessions were conducted three times including the interview session. The participants of this research are one English teacher and twenty-four of a secondary high school student. This research showed that the teacher in EFL classroom provided 5 types of corrective feedback namely recast, explicit correction, clarification request, metalinguistic feedback, and repetition. The findings revealed that the most used corrective feedback is recast and explicit correction is the second most used corrective feedback while metalinguistic feedback is the most less used corrective feedback. Regarding the students’ attitude towards corrective feedback, the interview indicates that there is no negative feedback found in this study. The students indicate positive acceptance towards the different type of feedback used by the teacher. This research also points out the importance of using corrective feedback in teaching English in EFL classrooms with Recast as the most frequently corrective feedback type used by the teacher in the classroom which is parallel with the previous studies.